The adoption of Davao branding system a case study on Sulu orchids farm - Mateo, Kathy Mar S.
The single-case study was conducted to explore the adoption process of SUL Orchids of Davao Branding program, and to identify all the factors that influenced such process. Roger's Diffusion of Innovation theory was used as an aid in organizing, presenting, analyzing the data. A long interview with the SUL Orchids Farm Manager, Mrs. Salvacion U. Leuenberger was done to gather all the necessary information. Moreover, short inquiries were also conducted with the program director of the Davao Branding Program, Ms. Mary Anne Abundo, the program assistant, Ms. Janine Joie Catadman and the SME Center in-charge, Ms. Jeni Hinlo through phone calls and short visits at the DCCCII office. Davao Branding documents were also used as supplementary data for the study. The study found out that the adoption of the SUL Orchids was exceptionally fast, not just because the program was free, but also because of the innovative personality of Mrs. Luenberger, her vision for the enterprise, and the status of the enterprise at the time of the adoption happened. The study has also confirmed that the success of diffusing an innovation does not solely rely on the characteristics of the innovation; it is the social context that strongly determines whether an adoption is possible.